2013
DOI: 10.1002/joc.3791
|View full text |Cite
|
Sign up to set email alerts
|

Improved simulation of Indian summer monsoon in latest NCEP climate forecast system free run

Abstract: Simulation of Indian summer monsoon features by latest coupled model of National Centers for Environmental Prediction (NCEPs) Climate Forecast System version 2 (CFSv2) is attempted in its long run. Improvements in the simulation of Indian summer monsoon as compared with previous version (CFSv1) is accessed and areas which still require considerable refinements are introduced. It is found that, spatial pattern of seasonal mean rainfall and wind circulations are more realistic in CFSv2 as compared with CFSv1. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
127
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 101 publications
(139 citation statements)
references
References 77 publications
(101 reference statements)
9
127
0
Order By: Relevance
“…Shukla and Kinter (2014) found that CFSv1 is not able to reproduce the observed ENSO-ISM relationship in rainfall anomalies. Saha et al (2014a) demonstrated that CFSv2 produces better spatial patterns of seasonal mean rainfall and circulation over extended Indian domain than CFsv1 does but the central Indian dry bias and cold SST bias in the Indian Ocean still persist in CFSv2. Shin and Huang (2015) further noticed that, in comparison with observations, CFSv2 generally simulates an earlier monsoon onset and stronger and longer lasting dry breaks and wet episodes that are phased-locked to the seasonal cycle in the ISM region.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Shukla and Kinter (2014) found that CFSv1 is not able to reproduce the observed ENSO-ISM relationship in rainfall anomalies. Saha et al (2014a) demonstrated that CFSv2 produces better spatial patterns of seasonal mean rainfall and circulation over extended Indian domain than CFsv1 does but the central Indian dry bias and cold SST bias in the Indian Ocean still persist in CFSv2. Shin and Huang (2015) further noticed that, in comparison with observations, CFSv2 generally simulates an earlier monsoon onset and stronger and longer lasting dry breaks and wet episodes that are phased-locked to the seasonal cycle in the ISM region.…”
Section: Introductionmentioning
confidence: 94%
“…Both CFSv2 and its predecessor, CFSv1, have shown considerable skill of seasonal prediction in tropics (e.g., Saha et al 2010Saha et al , 2014b. Using long-term simulations and seasonal hindcasts, many previous studies have examined different aspects of the seasonal and interannual variability of the ASM in CFSv1 (e.g., Yang et al 2008;Achuthavarier et al 2012;Pokhrel et al 2012;Chaudhari et al 2013;Shukla and Kinter 2014) and CFSv2 (e.g., Jiang et al 2013;Saha et al 2014a;Zhu and Shukla 2013;Mishra and Li 2014), which have identified some major problems in these simulations and hindcasts. For instance, Chaudhari et al (2013) reported that CFSv1 shows dry (wet) rainfall bias concomitant with cold (warm) SST bias over east (west) equatorial Indian Ocean.…”
Section: Introductionmentioning
confidence: 98%
“…dry precipitation bias over Indian region, cold tropospheric temperature bias over globe). They have also pointed out that the ratio of convective to total rainfall is overestimated as compared to observation (Saha et al 2014). Previous studies by Li et al (2011) have demonstrated that in the convectional GCM framework the improvement of convective parameterization may have a limited impact on the total precipitation.…”
Section: Introductionmentioning
confidence: 91%
“…One reason is connected with the fact that the potential predictability limit of Asian monsoon is low as compared to other tropical climate systems (Goswami 1998;Goswami et al 2006). Second important reason is that the climate models are ineffective to simulate observed distribution and intensity of monsoon rainfall realistically (Dai 2006;Kripalani et al 2007;Saha et al 2014). Therefore following question arises-why do models have difficulty in simulating the monsoon rainfall?…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation